2021
DOI: 10.1038/s42004-020-00445-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient alkane oxidation under combustion engine and atmospheric conditions

Abstract: Oxidation chemistry controls both combustion processes and the atmospheric transformation of volatile emissions. In combustion engines, radical species undergo isomerization reactions that allow fast addition of O2. This chain reaction, termed autoxidation, is enabled by high engine temperatures, but has recently been also identified as an important source for highly oxygenated species in the atmosphere, forming organic aerosol. Conventional knowledge suggests that atmospheric autoxidation requires suitable st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 39 publications
(54 reference statements)
5
92
2
Order By: Relevance
“…Even at night, the concentration of ozone is rarely lower than 10 ppb, resulting from the weak titration of low NO. At the same time, the reaction between ozone and high concentrations of NO 2 can provide sufficient NO 3 radicals, dominating nocturnal degradation of certain VOCs (Wayne et al, 1991). The elevated mixing level of total aromatic hydrocarbons is one of the main characteristics of the atmosphere in densely populated areas, in addition to which there should be many alkanes and alkenes which cannot be observed by the PTR-TOF-MS (Fu et al, 2013;Xu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Even at night, the concentration of ozone is rarely lower than 10 ppb, resulting from the weak titration of low NO. At the same time, the reaction between ozone and high concentrations of NO 2 can provide sufficient NO 3 radicals, dominating nocturnal degradation of certain VOCs (Wayne et al, 1991). The elevated mixing level of total aromatic hydrocarbons is one of the main characteristics of the atmosphere in densely populated areas, in addition to which there should be many alkanes and alkenes which cannot be observed by the PTR-TOF-MS (Fu et al, 2013;Xu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…5). Recent work has showed that autoxidation is more common than previously thought (Wang et al, 2021), and more studies are needed to explore the oxidation mechanisms of anthropogenic aliphatics and to evaluate their contribution to SOA.…”
Section: Aliph-ooms Factormentioning
confidence: 99%
“…Recently, Noziere and Vereecken 36 reported how even the naked alkanes have the potential for H-shift reactions, but they are too slow to provide a significant competition for other RO 2 loss processes. Thus, bimolecular RO 2 reactions yielding RO (e.g., with NO, 81 RO 2 , or even HO 2 , 82 even multiple consecutive 33 ) seem pivotal for the initiation of alkane autoxidation and formation of HOM ( Figure 5 ).…”
Section: Challenges In Pathwaysmentioning
confidence: 99%
“…Note the special role of RO radicals in propagating the oxidation sequence. Reprinted with permission from ref ( 33 ). Copyright 2021 Springer Nature.…”
Section: Challenges In Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation